Enhanced photocatalytic properties of a chemically modified blue phosphorene - Maibam, Ashakiran; Das, Sawan Kumar; Samal, Pragnya Paramita; Krishnamurty, Sailaja (RSC Advances, 2021)
It is high time to placate the peak demand for an efficient, economic and green fuel in the form of H-2 through photocatalytic water splitting. Several low dimensional materials have been explored for their photocatalytic properties on account of their surface to volume ratio. The present study illustrates the excellent photocatalytic potential of a two-dimensional material, viz. a chemically tempered blue-phosphorene sheet, with single atom thickness and high carrier mobility. Metal-free element, sulphur, is explored as a dopant in a 32-atom blue-phosphorene sheet. The dopant is inserted at three locations viz. central, edge and central edge positions with varying concentrations from 3.125% to 18.75% (corresponding to n = 1 to 6 sulphur atoms within a 32-atom blue-phosphorene sheet, P32-nSn). The cohesive energy studies predict the higher stability of even number S doped sheets as compared to their odd counterparts. Photocatalytic activity is studied in terms of band gap and band alignment for different concentrations of the former. Studies reveal that edge doping demonstrates better water molecule activation independent of S atom concentration. The edge doped systems not only provide the chemical activity to activate water, but also show feasible HER overpotentials of 1.24-1.29 eV at neutral medium. Finally, this work opens up a driving lead of non-corrosive catalysts for water molecule splitting.

Expounding lemonal terpenoids as corrosion inhibitors for copper using DFT based calculations - Samal, Pragnya Paramita; Singh, Chandrodai Pratap; Krishnamurty, Sailaja (Applied Surface Science, 2023)
The most important bottleneck in identifying an innovative and yet viable corrosion inhibitor for copper surfaces is discerning the chemical interactions at the interface of adsorbate and adsorbent. The present work, primarily, discerns the interface chemistry of green corrosion inhibitors, viz., lemonal terpenoids, with the copper surfaces for the first time. The interface chemistry is evaluated for distinct facets of copper, modelled by periodic surfaces to finite sized aggregates, with two stereoisomers viz., citral and neral through density functional calculations. The adsorption/ interaction properties between the surface and the corrosion inhibiting molecule are analysed through the electronic properties such as density of states, charge density difference plots and Bader charges where in distinct bonding mechanisms are identified as a function of varying facets. Apart from the adsorption properties, molecular packing properties are of paramount importance towards the design of an efficient corrosion inhibitor for a surface. Hence, we also analyse the intermolecular stacking energies between the inhibitors when packed among themselves in vacuum and when adhered on to metal surfaces. The studies bring forth an understanding that lemon terpenoids are highly potential corrosion inhibitors for copper surfaces, particularly, for Cu (110) surfaces both in neutral and protonated form.
Keywords: Copper surface; Density Functional Theory (DFT); Green corrosion inhibitors; Interface chemistry; Lemonal terpenoids; Molecular stacking